Pharmacokinetics and Safety of Intravenous Peramivir, Neuraminidase Inhibitor of Influenza Virus, in Healthy Japanese Subjects. Issue 4 (May 2017) - Saisho, Yutaka; Ishibashi, Toru; Fukuyama, Hidenori; Fukase, Hiroyuki; Shimada, Jingoro
Background: Intravenous peramivir is a potent neuraminidase (NA) inhibitor with activity against influenza A and B viruses. The early use of NA inhibitors has been shown to reduce mortality in influenza patients. Methods: To evaluate the pharmacokinetics of peramivir and confirm the safety and tolerability of multiple infusions of peramivir in healthy Japanese subjects, two Phase I, single-centre, randomized, double-blind and placebo-controlled studies consisting of a multiple-dose study and a high-dose study were conducted. Results: Multiple intravenous infusions of peramivir were well tolerated up to 800 mg once a day and 400 mg twice daily for 6 days. Dose proportionalities for maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) were established up to the 800 mg dose. Approximately 90% of unchanged peramivir was excreted into urine within 12 h after treatment with 800 mg of peramivir. The peramivir plasma and upper respiratory tract fluid levels were significantly higher than the 50% inhibition concentrations for NA enzyme activity (IC50 ) of epidemic influenza viruses, including those harbouring the H274Y mutation. Conclusions: The pharmacokinetic properties obtained here for intravenous peramivir are consistent with the previously reported clinical efficacy and safety of this antiviral.